ISLAMIC EDUCATION MANAGEMENT STRATEGIES FOR SDG 4: EDUCATION COMPARISON INDONESIA AND TURKIYE - Muhammad Rizki Syahputra; Wahyu Iskandar; Masringgit Marwiyah Nst; Mahdi Handayani Sidik (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2026)
Despite growing scholarly interest in Islamic education reform, empirical comparative studies examining how Madrasah Ibtidaiyah (MI) in Indonesia operationalize institutional management strategies to meet modernity's demands, benchmarked against internationally recognized models such as Turkey's Imam Hatip schools, remain absent from Scopus-indexed literature. This research gap motivated a qualitative multi-site case study at three MI in North Sumatra, Indonesia, complemented by cross-national comparative analysis with Turkish Imam Hatip schools, aimed at identifying, theorizing, and benchmarking management strategies that align with Sustainable Development Goal 4 (SDG 4). Data were gathered through semi-structured interviews with 18 institutional stakeholders across three MI in Deli Serdang and Medan, participant observation, and institutional document analysis over six months. Five strategic dimensions emerged: (1) integrative curriculum design combining Kurikulum Merdeka with Islamic studies; (2) character-based pedagogy embedded in daily Islamic routines; (3) participatory musyawarah governance; (4) ethically framed digital integration; and (5) teacher professionalism reinforced through PPG Madrasah certification. Comparative analysis reveals that while MI and Imam Hatip schools share foundational Islamic educational values, Turkey demonstrates stronger state-institutional coherence and systematized teacher formation, whereas MI exhibit greater community-driven governance flexibility. These findings offer a replicable governance framework for Indonesian MI reform and inform SDG 4 policy implementation within Muslim-majority educational systems.